2021
DOI: 10.3390/pathogens10111414
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Detection of Equine Piroplasms Using Multiplex PCR and First Genetic Characterization of Theileria haneyi in Egypt

Abstract: Equine Piroplasmosis (EP) is an infectious disease caused by the hemoprotozoan parasites Theileria equi, Babesia caballi, and the recently identified species T. haneyi. Hereby, we used a multiplex PCR (mPCR) targeting the 18S rRNA gene of T. equi and B. caballi for the simultaneous detection of EP in Egyptian equids and examined the presence of T. haneyi infections in Egypt. Blood samples from 155 equids (79 horses and 76 donkeys) collected from different governorates of Egypt were examined by mPCR and PCR tar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 52 publications
0
17
0
1
Order By: Relevance
“…Biomolecular detection methods have developed rapidly in recent years. Particularly, owing to its high sensitivity and specificity, PCR technology has been established as the best method for detecting and differentiate EP ( 15 , 26 , 31 ). Previous studies have shown that nPCR is more sensitive and specific than traditional PCR in detecting EP ( 9 , 16 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Biomolecular detection methods have developed rapidly in recent years. Particularly, owing to its high sensitivity and specificity, PCR technology has been established as the best method for detecting and differentiate EP ( 15 , 26 , 31 ). Previous studies have shown that nPCR is more sensitive and specific than traditional PCR in detecting EP ( 9 , 16 , 19 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regardless of the fact that these equines play significant role in sustaining the daily lives of people by providing support in industries such as agriculture, construction, tourism, and public transportation. However, the health and welfare of domesticated equines is frequently overlooked [ 1 ].…”
Section: Introductionmentioning
confidence: 99%
“…Equine piroplasmosis (EP) is a tick-borne protozoal disease of horses, donkeys, zebras, and mules caused by the haemoprotozoan parasites Theileria equi, Babesia caballi [1], and T. haneyi (newly identified species) [2,3]. The disease affects red blood cells [1][2][3], and in the literature, it has been referred to as equine malaria, biliary equine fever, and tick-borne fever and has affected all species of Equidae [4].…”
Section: Introductionmentioning
confidence: 99%
“…Equine piroplasmosis (EP) is a tick-borne protozoal disease of horses, donkeys, zebras, and mules caused by the haemoprotozoan parasites Theileria equi, Babesia caballi [1], and T. haneyi (newly identified species) [2,3]. The disease affects red blood cells [1][2][3], and in the literature, it has been referred to as equine malaria, biliary equine fever, and tick-borne fever and has affected all species of Equidae [4]. It has endemic characteristics in most parts of the world, with significant clinical and economic consequences due to the necessary treatment, the decreased output of animals, and the negative impact on international trade [5,6].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation